Mutation rates: simpler than we thought? - Brookfield, John F.Y. (Elsevier (Cell Press), 2018)
Mutation rate variation is often explained by varying optimal rates, or through effective population sizes determining the effectiveness of selection. But a rate difference between humans and owl monkeys is now explained mechanistically as a consequence of differing reproductive longevities.